Pelatihan Relawan Ambulan Desa dalam Menghadapi Gawat Darurat Sehari-hari dan Bencana - Aurick Yudha Nagara; Rose Khasana Dewi; Diah Royani Meisani; Rajveer Singh Mann; Nofita Dwi Harjayanti; Nur Syamsu Dhuha; Muhammad Rayyan Doli Rangkuty; Jessica Anna Sallvia (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Pre-hospital emergency care is a critical component of the Emergency Medical Services (SPGDT) to mitigate mortality and disability rates. However, village ambulance volunteers, acting as Community First Responders (CFR), frequently encounter a discrepancy between their significant responsibilities and limited clinical competencies, compounded by logistical deficits. This community service initiative aims to enhance the basic medical competence of village ambulance volunteers through structured training interventions. The implementation utilized a collaborative approach with an emphasis on hands-on practice and real-world scenarios. Data were qualitatively analyzed using Reflexive Thematic Analysis based on observations and focused discussions. The analysis identified three primary themes: (1) clinical skill deficits posing risks of evacuation malpractice (improper lifting), (2) logistical gaps in standard ambulance equipment, and (3) the efficacy of practice-based and simulation training methods. The training significantly improved participants' knowledge, technical skills (CPR, spinal stabilization, triage), and self-confidence. These findings underscore the necessity of standardizing ambulance logistics through village budgets and developing a Training of Trainers (ToT) model to ensure the sustainability of community-based health resilience.